Marketing basics for designers : - Martin, Jane D. (John Wiley & Sons, 1995)
This book meets a great need in the design field for a professional marketing resource focusing on small design firms (1-4 person firms). This book was developed as a resource for these designers, to aid in finding new clients and marketing design services. It includes a basic, practicalreat need in the design field for a professional marketing resource focusing on small design firms (1-4 person firms). This book was developed as a resource for these designers, to aid in finding new clients and marketing design services. It includes a basic, practical approach, and takes into account that the typical interior designer is also managing an office and a variety of projects in addition to preparing a marketing strategy. It offers suggestions and guidance for marketing with such obstacles as limited funds, no time, and few resources, and includes a list of ideas to get readers started on their own marketing projects.